Pokazateli spetsialnoj fizicheskij podgotovlennosti vysokokvalifitsirovannykh sportsmenok v khudozhestvennoi gimnastike - Gorokhova, V. E. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The investigations of athletes in gymnastics showed, that they are good developed in strength, lexibility and speed. Not so good developed are endurance and the ability to maintain balance. Bad results showed the data for speed-strength and the work with devices.